Innovative design of waste processing technologies - Safronova, Natalya; Khaibrakhmanova, Gulnaz (Serbian Journal of Management, 2021)
Designing modern waste recycling systems is an urgent problem. The experience of attracting masters from two leading Russian universities in organizing interaction and cooperation in the development and implementation of waste sorting complexes is considered. Faculties of Russian Academy of National Economy and Public Administration and Moscow Institute of Physics and Technology held a project session for developing and launching innovative technological projects on the market called “Techno marketing”. The developed methodological base made it possible to combine educational and entrepreneurial tasks and ensure the promotion of student technological projects. As a result of the conducted project session, a project on the use of computer vision systems for sorting waste was developed, the competitive differences of the project and its technical and economic indicators were presented. The mechanisms for the implementation of an innovative waste sorting project have been determined. Despite being twice as expensive, the waste sorting machine is able to fully pay off 3 times faster than manual sorting, justifying further investment in the project.